The Influence of Trust, Perceived Usefulness, and Pleasure on Repurchase Interest (Study on Online Shop Customers JD.id in Yogyakarta City) - Ilham Tryrachma (Economos : Jurnal Ekonomi dan Bisnis, 2023)
In Indonesia, the growth of the E-commerce industry is one of the industries that has experienced very significant development. E-commerce is all buying and selling activities carried out through electronic media. The purpose of this study is to find out: (1) the effect of trust on repurchase intention on JD.id online store customers in Yogyakarta City, (2) the effect of usability perception on repurchase intention on JD.id online store customers in Yogyakarta City, (2) the effect of benefit perception on repeat purchase intention in JD.id online store customers in Yogyakarta City. City, (3) the effect of satisfaction on repurchase interest in JD online store customers. id in Yogyakarta City, and (4) the influence of trust, perception of benefits, and pleasure on the repurchase intention of JD.id online shop customers in Yogyakarta City. This study used quantitative methods. The population in this study is all customers who have purchased products/goods through JD.id online store in the city of Yogyakarta. The sampling technique with purposive sampling obtained a total sample of 125 people. Data collection using questionnaires that have been tested for validity and reliability. Classical assumption tests include: normality test, multicollinearity test, and heteroscedasticity test. The data analysis technique uses multiple linear regression. The results showed that: (1) trust has a positive effect on the repurchase intention of JD.id online store customers in Yogyakarta City, (2) benefit perception has a positive effect on the repurchase intention of JD.id online store customers in Yogyakarta City, (3) pleasure has a positive effect on the repurchase intention of JD online store customers. id in the city of Yogyakarta, and (4) trust, perceived benefits, and enjoyment affect repurchase intentions in JD online store customers. en in Yogyakarta City.